Tunable, low frequency microwave generation from AWG based closely-spaced dual-wavelength single-longitudinal-mode fibre laser - Ahmad, Harith; Latif, A.A.; Talib, J.M.; Harun, Sulaiman Wadi (European Optical Society, 2013)
Stable, closely-spaced Dual-Wavelength Fibre Lasers (DWFLs) have high potential for applications such as Radio-over-Fibre and optical sensing. In this work, a DWFL using two Arrayed Waveguide Gratings (AWGs) to generate a closely-spaced dual-wavelength output is proposed and demonstrated. A 1 m long highly doped Leikki Er80-8/125 Erbium Doped Fibre (EDF) is used as the linear gain medium, while two AWGs are used to generate the closely-spaced lasing wavelengths. A Mach-Zehnder modulator, driven at 180 kHz, splits the closely spaced wavelengths into two clearly defined wavelengths, while a 7 cm long un-pumped Leikki Er80-8/125 EDF and sub-ring cavity is used to suppress unwanted side-modes. Close spacing of between 0.01 to 0.03 nm are obtained, with beating frequencies of between 1.4 to 3.2 GHz. The output is highly stable, with almost no fluctuations over the test period.